IMPLIKASI MEKANISMECORPORATE GOVERNANCE, LEVERAGE, AUDIT TENURE DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - Ida Ayu Ratih Manuari; Ni Luh Nyoman Sherina Devi (Journal of Applied Management and Accounting Science, 2021)
Financial reports are used by entities to convey financial conditions tostakeholders. Financial reports are expected to have integrity, which means that they have truthful and reliable information.This study aims to analyze the effect of corporate governance mechanisms, leverage, audit tenure and audit quality on the integrity of financial statements in financial sector companies listed on the Indonesia Stock Exchange.The sample was selected using a purposive sampling method. The data analysis technique used is multiple linear regression. The results showed that institutional ownership, managerial ownership, independent commissioners, and audit committee had no effect on the integrity of financial statements. Leverage and audit tenure were found to have a negative effect, and audit quality has a positive effect on the integrity of financial statements.Therefore, companies are expected to pay attention to the level of leverage ratios and audit services, thus the level of integrity of financial statements can always be improved.